RANCANG BANGUN APLIKASI LAYANAN BIMBINGAN KONSELING BERBASIS WEBSITE DI SMA MUHAMMADIYAH 1 TAMAN SIDOARJO - Zaki Abdurrahman Zain; Sulistiowati Sulistiowati; Norma Ningsih (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
SMA Muhammadiyah 1 Taman Sidoarjo is a private school located at Jalan Raya Kategan No. 35. SMA Muhammadiyah 1 Taman has several processes of counseling activities including recording counseling services, recording solutions, recording follow-up reports, making counseling reports, and history of counseling services. In this activity, recording was carried out using a counseling service book which was stored in a filing cabinet in the Counseling room. Then search for counseling service data in the counseling service form book which can take 5 (five) minutes to carry out the search process. The history of counseling services is very influential in the process of counseling services, from this history counselors can understand the personality of students, and counselors can provide the best solution or treatment of problems faced by students. To overcome these problems, a web-based counseling service application design was made at SMA Muhammadiyah 1 Taman Sidoarjo which was integrated with the SDLC (System Development Life Cycle) method and used Waterfall development. The results of the application design for web-based counseling services at SMA Muhammadiyah 1 Taman Sidoarjo include a list of students, a list of homeroom teachers, a list of classes, a list of types of counseling services that contains a list of each student and class and homeroom teacher and the types of counseling services available, namely academic, social, family and personal. In addition, the master of recording counseling services, master of counseling service solutions, master of follow-up counseling services that can be used in recording counseling, then searching for counseling data and history of counseling services which can be done in less than 15 (fifteen) seconds in the counseling report form used in the recap. for the principal. Then the notification to the guardian of the student using whatsapp messenger is used to notify the guardian of the student if his child gets counseling guidance. The test results of the application with black-box testing are that every function of the test scenario, test case, and application output has been spared from bugs or errors.